Is any defect in Islamic banking products? a case study of BBA - Syed, Ahmed Salman; Htay, Sheila Nu Nu (Choice College of Arts & Commerce, Pune., 2013)
The rapid growth of Islamic banking and finance plays significant role to provide the financing facility for both Muslims and non-Muslims. One of the most popular Islamic banking products for property financing is Bay‟ Bithaman Ajil (BBA). It has been widely used in Malaysian banking environment although this type of product is not allowed in Middle East. When BBA is used to finance for any incomplete property, the unethical problems arise. It is because the banks are forcing the customers to pay and at the end, the customer does not occupy the property and at the same time, they are in debt. Banks should be taking responsibility, rather than putting the entire burden on the customers, in the case of default by property developer. This paper suggests the regulators, industry players and shari‟ah scholars to revisit the validity issue of BBA financing for the incomplete product.